Gender, race, and mourning in American modernism - Forter, Greg; Cambridge (Online service). (Cambridge Cambridge University Press, 2011)
American modernist writers' engagement with changing ideas of gender and race often took the form of a struggle against increasingly inflexible categories. Greg Forter interprets modernism as an effort to mourn a form of white manhood that fused the 'masculine' with the 'feminine'. He argues that modernists were engaged in a poignant yet deeply conflicted effort to hold on to socially 'feminine' and racially marked aspects of identity, qualities that the new social order encouraged them to disparage. Examining works by F. Scott Fitzgerald, Ernest Hemingway, William Faulkner and Willa Cather, Forter shows how these writers shared an ambivalence toward the feminine and an unease over existing racial categories that made it difficult for them to work through the loss of the masculinity they mourned. Gender, Race, and Mourning in American Modernism offers a bold new reading of canonical modernism in the United States - Provided by publisher.
Introduction -- 1. Gender, melancholy, and the whiteness of impersonal form in The Great Gatsby -- 2. Redeeming violence in The Sun Also Rises: phallic embodiment, primitive ritual, fetishistic melancholia -- 3. Versions of traumatic melancholia: the burden of white man's history in Light in August and Absalom, Absalom! -- 4. The Professor's House: primitivist melancholy and the gender of Utopian forms.
Electronic reproduction.
Keywords: American fiction -- History and criticism. -- 20th century; Modernism (Literature) -- United States; Gender identity in literature; Race in literature; Grief in literature; Electronic books